A study of the genus Neocerambyx J. Thomson (Coleoptera: Cerambycidae: Cerambycinae: Cerambycini) from China, with the description of a new species - Lin, Mei-Ying; Zhang, Bing-Lan (Zootaxa, 2026)
One new species of the genus Neocerambyx J. Thomson, 1861, N. huai Lin & Zhang, sp. nov. is described from Guangdong, China. The genitalia pictures and descriptions are provided for three recently published species: N. liyuani Lin, Miroshnikov & He, 2025, N. miaobenfui Lin, Miroshnikov & He, 2025, and N. gui Lin, Miroshnikov & He, 2025. Neocerambyx atratulus (Holzschuh, 2018) from Mêdog, Xizang is recorded from China for the first time.